Education in South-East Asia - Symaco, Lorraine Pe, 1978- (London : Bloomsbury Academic, 2013)
Education in South-East Asia is a comprehensive critical reference guide to education in South East Asia. With chapters written by an international team of leading regional education experts, the book explores the education systems of the ten member states of the Association of South-East Asian Nations (ASEAN) and the state of Timor-Leste. The diverse range and forms of culture, religion and politics embedded in the region are exhibited in the distinctive education systems that inter-relate in one of the most integrated regions in the world. Including a comparative introduction to the issues f.
Lorraine Pe Symaco11 The Philippines: Higher Education and Development; Lorraine Pe Symaco; 12 Singapore: Education in Transition; Letchmi Ponnusamy and Saravanan Gopinathan; 13 Singapore: The Malay Ethnic Minority -- Playing Perennial Catch-up in Education?; Jason Tan; 14 Thailand: Issues in Education; Chaiyuth Punyasavatsut; 15 Timor-Leste: Education, Decolonization and Development; Bob Boughton; 16 Vietnam: The Education System -- A Need to Improve Quality; Martin Hayden and Le Thi Ngoc Lan; Index.
Includes bibliographical references and index.
Keywords: Comparative education; Education -- Southeast Asia; Education -- Aims and objectives -- Southeast Asia; International education